Evaluation of mortality among Marines, Navy personnel, and civilian workers exposed to contaminated drinking water at USMC base Camp Lejeune: a cohort study - Frank J. Bove; April Greek; Ruth Gatiba; Rona C. Boehm; Marcie M. Mohnsen (BMC, 2024)
Abstract Background Drinking water at U.S. Marine Corps Base (MCB) Camp Lejeune, North Carolina was contaminated with trichloroethylene and other industrial solvents from 1953 to 1985. Methods A cohort mortality study was conducted of Marines/Navy personnel who, between 1975 and 1985, began service and were stationed at Camp Lejeune (N = 159,128) or MCB Camp Pendleton, California (N = 168,406), and civilian workers employed at Camp Lejeune (N = 7,332) or Camp Pendleton (N = 6,677) between October 1972 and December 1985. Camp Pendleton's drinking water was not contaminated with industrial solvents. Mortality follow-up was between 1979 and 2018. Proportional hazards regression was used to calculate adjusted hazard ratios (aHRs) comparing mortality rates between Camp Lejeune and Camp Pendleton cohorts. The ratio of upper and lower 95% confidence interval (CI) limits, or CIR, was used to evaluate the precision of aHRs. The study focused on underlying causes of death with aHRs ≥ 1.20 and CIRs ≤ 3. Results Deaths among Camp Lejeune and Camp Pendleton Marines/Navy personnel totaled 19,250 and 21,134, respectively. Deaths among Camp Lejeune and Camp Pendleton civilian workers totaled 3,055 and 3,280, respectively. Compared to Camp Pendleton Marines/Navy personnel, Camp Lejeune had aHRs ≥ 1.20 with CIRs ≤ 3 for cancers of the kidney (aHR = 1.21, 95% CI: 0.95, 1.54), esophagus (aHR = 1.24, 95% CI: 1.00, 1.54) and female breast (aHR = 1.20, 95% CI: 0.73, 1.98). Causes of death with aHRs ≥ 1.20 and CIR > 3, included Parkinson disease, myelodysplastic syndrome and cancers of the testes, cervix and ovary. Compared to Camp Pendleton civilian workers, Camp Lejeune had aHRs ≥ 1.20 with CIRs ≤ 3 for chronic kidney disease (aHR = 1.88, 95% CI: 1.13, 3.11) and Parkinson disease (aHR = 1.21, 95% CI: 0.72, 2.04). Female breast cancer had an aHR of 1.19 (95% CI: 0.76, 1.88), and aHRs ≥ 1.20 with CIRs > 3 were observed for kidney and pharyngeal cancers, melanoma, Hodgkin lymphoma, and chronic myeloid leukemia. Quantitative bias analyses indicated that confounding due to smoking and alcohol consumption would not appreciably impact the findings. Conclusion Marines/Navy personnel and civilian workers likely exposed to contaminated drinking water at Camp Lejeune had increased hazard ratios for several causes of death compared to Camp Pendleton.